2022
DOI: 10.3390/diagnostics12010163
|View full text |Cite
|
Sign up to set email alerts
|

Development and Verification of an Adjustment Factor for Determining the Axial Length Using Optical Biometry in Silicone Oil-Filled Eyes

Abstract: The aim of this prospective clinical study was to establish and verify an adaptation for axial length (AL) measurement in silicone oil (SO)-filled pseudophakic eyes with a Scheimpflug and partial coherence interferometry (PCI)-based biometer. The AL was measured with a Pentacam AXL (OCULUS Optikgeräte GmbH, Wetzler, Germany) and IOLMaster 700 (Carl Zeiss Meditec, Jena, Germany). The coefficients of variation (CoV) and the mean systematic difference (95% confidence interval (CI)) between the devices were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Measuring AL in SO-lled eyes brings additional challenges: artifacts caused by oil droplets may complicate the measurement, and insu cient SO lling in different degrees may lead to deviations in the results, especially in ultrasound biometry where patients are in a prone position 7,21 . CoV can be used to indicate the accuracy and repeatability of measurement 22 . The lower the CoV value, the higher the precision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring AL in SO-lled eyes brings additional challenges: artifacts caused by oil droplets may complicate the measurement, and insu cient SO lling in different degrees may lead to deviations in the results, especially in ultrasound biometry where patients are in a prone position 7,21 . CoV can be used to indicate the accuracy and repeatability of measurement 22 . The lower the CoV value, the higher the precision.…”
Section: Discussionmentioning
confidence: 99%
“…The lower the CoV value, the higher the precision. Auffarth et al 22 used Pentacam AXL and IOLMaster 700 to measure the AL of pseudophakic SO-lled eyes. Their research showed that the CoV of Pentacam AXL and IOLMaster 700 were 0.26% and 0.09% respectively.…”
Section: Discussionmentioning
confidence: 99%